2020
DOI: 10.3390/agronomy10121846
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Growth and Photosynthesis of Kimchi Cabbage According to Extreme Weather Conditions

Abstract: The aim of this study was to develop and validate growth and photosynthetic models of Kimchi cabbages under extreme temperature conditions at different growth stages. Kimchi cabbage plants were subjected to low and high air temperatures 7–10 days after transplanting (DAT) and 40–43 DAT using extreme weather simulators. Except during these periods, the air temperature, relative humidity, solar radiation, and precipitation were set according to previous meteorological data. The experiments were performed over tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Beyond the optimum limit leaf temperature (optimum planting time) inhibits the photosynthetic rate by stimulating photorespiration and cause damages to photosynthetic apparatus (Schrader et al 2004;Rasmusson et al 2020). Rubisco activity is reduced at moderate elevation in leaf temperature resultantly reduce photosynthetic rate (Salvucci et al 2001;Wi et al 2020). All these studies showed that photosynthesis and water use efficiency are leaf temperature dependent attributes.…”
Section: Discussionmentioning
confidence: 96%
“…Beyond the optimum limit leaf temperature (optimum planting time) inhibits the photosynthetic rate by stimulating photorespiration and cause damages to photosynthetic apparatus (Schrader et al 2004;Rasmusson et al 2020). Rubisco activity is reduced at moderate elevation in leaf temperature resultantly reduce photosynthetic rate (Salvucci et al 2001;Wi et al 2020). All these studies showed that photosynthesis and water use efficiency are leaf temperature dependent attributes.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, Cd stress was suggested to significantly influence the electron transfer in the mitochondrion and chloroplast, possibly via causing chloroplast swelling and deformation, disintegration of cystoid, increase of starch granules, and loose and disordered arrangement of mitochondrial basal lamellae in plants [11,36]. It has also been pointed out that Cd stress can effectively inhibit photosynthetic processes such as light energy uptake, energy conversion, Rubisco's enzyme carboxylation reaction, and CO 2 diffusion in leaves (Sagardoy et al, 2010;Wi et al, 2020) [43,44]. These may explain the rapid decrease in chlorophyll synthesis and the photosynthetic rate in plants under Cd stress.…”
Section: Discussionmentioning
confidence: 99%
“…If the maximum and minimum inflection points of cabbage growth acceleration ar differentiated by length, the value will be 0. 17) is obtained by solving the quadratic equation for Equation (16).…”
Section: 𝑑𝑎(𝑡) 𝑑𝐺(𝑡)mentioning
confidence: 99%
“…The growth of Kimchi cabbage is affected by natural factors such as temperature [12], soil moisture [13], and irrigation [14] and depends on the growing season and moisture conditions. This means that cabbage growth has properties that vary in response to climatic and soil conditions [15,16]. The growth process of Kimchi cabbage shows spatial variations in the stems and leaves depending on factors related to soil, moisture, and temperature.…”
Section: Introductionmentioning
confidence: 99%